Non-exhaustive double effort test is reliable and estimates the first ventilatory threshold intensity in running exercise - Lucas Dantas Maia Forte; Fúlvia Barros Manchado-Gobatto; Roberta Cunha Matheus Rodrigues; Maria Cecília Gallani; Claudio Alexandre Gobatto (Elsevier, 2018)
Purpose: The present study aimed to investigate the reliability of the non-exhaustive double effort (NEDE) test in running exercise and its associations with the ventilatory thresholds (VT1 and VT2) and the maximal lactate steady state (MLSS). Methods: Ten healthy male adults (age: 23 ± 4 years, height: 176.6 ± 6.4 cm, body mass: 76.6 ± 10.7 kg) performed 4 procedures: (1) a ramp test for VT1 and VT2 determinations measured by ratio of expired ventilation to O2 uptake (VE/VO2) and expired ventilation to CO2 output (VE/VCO2) equivalents, respectively; (2) the NEDE test measured by blood lactate concentration (NEDELAC) and heart rate responses (NEDEHR); (3) a retest of NEDE for reliability analysis; and (4) continuous efforts to determine the MLSS intensity. The NEDE test consisted of 4 sessions at different running intensities. Each session was characterized by double efforts at the same running velocity (E1 and E2, 180 s), separated by a passive recovery period (90 s rest). LAC and HR values after E1 and E2 (in 4 sessions) were used to estimate the intensity equivalent to "null delta" by linear fit. This parameter represents, theoretically, the intensity equivalent to maximal aerobic capacity. Results: The intraclass correlation coefficient indicated significant reliability for NEDELAC (0.93) and NEDEHR (0.79) (both p < 0.05). There were significant correlations, no differences, and strong agreement with the intensities predicted by NEDELAC (10.1 ± 1.9 km/h) and NEDEHR (9.8 ± 2.0 km/h) to VT1 (10.2 ± 1.1 km/h). In addition, despite significantly lower MLSS intensity (12.2 ± 1.2 km/h), NEDELAC and NEDEHR intensities were highly correlated with this parameter (0.90 and 0.88, respectively). Conclusion: The NEDE test applied to running exercise is reliable and estimates the VT1 intensity. Additionally, NEDE intensities were lower but still correlated with VT2 and MLSS. Keywords: Aerobic exercise, Anaerobic threshold, Maximal lactate steady state, Non-exhaustive protocol, Training prescription, Ventilatory threshold